2017
DOI: 10.1016/j.eurpsy.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in a cohort of individuals with Prader–Willi syndrome

Abstract: Psychiatric diagnoses are very frequent in PWS and strongly influence QOL. Furthermore, characterizing the profile of psychiatric comorbidity in PWS is crucial for planning effective interventions. Precise behavioral phenotyping in PWS in combination with a well-defined genetic etiology may aid biological research linking biological correlates to behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The results of our novel detailed neuropsychiatric diagnostic and genetic study in adults with PWS in residential care further support the observations of psychiatric features with compulsions and skin picking as common findings. 8 Several psychiatric or behavioral problems were treated with a variety of medications in our PWS adult cohort including: mood stabilizers including lithium carbonate; selective serotonin reuptake inhibitors (SSRIs); serotonin/norepinephrine reuptake inhibitors (SNRI); N-acetyl cysteine (for skin picking); atypical antipsychotics; occasional benzodiazepines; rare use of stimulant and occasionally antiadrenergic agents. Differences were also seen in accumulated number of psychiatric diagnoses and BMI in those with the larger 15q11-q13 Type I deletion but only when adjusted for age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our novel detailed neuropsychiatric diagnostic and genetic study in adults with PWS in residential care further support the observations of psychiatric features with compulsions and skin picking as common findings. 8 Several psychiatric or behavioral problems were treated with a variety of medications in our PWS adult cohort including: mood stabilizers including lithium carbonate; selective serotonin reuptake inhibitors (SSRIs); serotonin/norepinephrine reuptake inhibitors (SNRI); N-acetyl cysteine (for skin picking); atypical antipsychotics; occasional benzodiazepines; rare use of stimulant and occasionally antiadrenergic agents. Differences were also seen in accumulated number of psychiatric diagnoses and BMI in those with the larger 15q11-q13 Type I deletion but only when adjusted for age.…”
Section: Discussionmentioning
confidence: 99%
“…In early childhood, food seeking and hyperphagia generally occurs leading to onset of obesity which can be life‐threatening, if uncontrolled. Intellectual disability for the family background and behavioral problems including mood instability, tantrums, obsessive and compulsive behaviors, stubbornness, aggression and skin picking are common and frequently occur in childhood and continue into adulthood, recently supported in a cohort of 53 adults and adolescents with PWS and the overwhelming majority (89%) had at least one psychiatric diagnosis . The most common observation was disruptive behavior disorder (68%) followed by obsessive compulsive disorder (45%) and skin picking (35%).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show a worsening in maladaptive behavior with lower BMI (Hartley et al, 2005; Sinnema et al, 2011), while others have described negative correlations with BMI and scores on the Developmental Behavior Checklist for adults (DBC‐A) after controlling for genetic subtype (Jauregi et al, 2013; Steinhausen et al, 2004). Shriki‐Tal et al, found no correlation between BMI and psychiatric disorders (Shriki‐Tal et al, 2017). Compared to the individuals living at home, the hostel residents received more psychiatric medications, which might reflect more severe behavioral or psychiatric disorders in this group.…”
Section: Discussionmentioning
confidence: 99%
“…OCD symptoms often increase in severity and rigidity as children with PWS age (Dykens et al, 1996), and occur at higher rates than in children with other developmental disabilities (Dimitropoulos et al, 2001(Dimitropoulos et al, , 2006State et al, 1999). In adulthood, 10% to 20% of individuals with PWS meet criteria for psychosis (Boer et al, 2002;Larson et al, 2014;Shriki-Tal et al, 2017), which often has an intermittent course (Soni et al, 2007).…”
Section: Language Ability Unlike Individuals Withmentioning
confidence: 99%